Auditing awareness: a corpus-driven approach / Aeisha Joharry and Hairani Wahab - Joharry, Aeisha; Wahab, Hairani (2019)
Auditing is characterized by the reliance on a number of principles. These principles should help to make the audit an effective and reliable tool in support of management policies and controls, by providing information on which an organization can act in order to improve its performance (ISO 19011:2011). However, many people are put off by the word audit and this may be due to a lack of knowledge or awareness on the importance of audit process and findings. In this study, an exploratory approach is taken to investigate words that are used to describe the auditing process via corpus methods/techniques. A copy of the Code of Practice for Institutional Audit (COPIA) document obtained from the MQA website is built into a corpus, which is then extracted using corpus software to examine frequent words and phrases. Following this, comparison is made to a guideline document used in UiTM's quality assurance activity known as Guidelines for Integrated Audit (IQMS). Analyses of the quantitative search and particular phrases are then reflected on the particular communicative function (i.e. auditing processes). Findings are descriptive in that results are hoped to enhance further understanding of the COPIA document as well as auditing as a whole.